2020
DOI: 10.1108/ajim-10-2019-0299
|View full text |Cite
|
Sign up to set email alerts
|

“We Need Psychological Support”: the information needs and seeking behaviors of African refugees in the United States

Abstract: PurposeThe purpose of this study is to examine the information needs and seeking behaviors of African refugees in the Midwest United States. The research also investigates the sources participants consulted and their satisfaction with their information seeking and the information found.Design/methodology/approachThis qualitative research study recruited 18 African refugees to participate in one or more data collection modes used in the study (questionnaire, interview, focus group). The data were analyzed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Information seeking behaviour during life-changing events has received great attention within the field of information behaviour including the information needs and seeking behaviours of refugees (Hassan and Wolfram, 2020), concerned working students during a haze crisis (Pang, 2014) and during extreme weather (Silver and Andrey, 2019). Health information seeking behaviour is an area where the information an individual finds impact their lifestyle and health behaviours in both long and short terms (Zhang, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Information seeking behaviour during life-changing events has received great attention within the field of information behaviour including the information needs and seeking behaviours of refugees (Hassan and Wolfram, 2020), concerned working students during a haze crisis (Pang, 2014) and during extreme weather (Silver and Andrey, 2019). Health information seeking behaviour is an area where the information an individual finds impact their lifestyle and health behaviours in both long and short terms (Zhang, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Mansour (2018) on Syrian refugees displaced to Egypt revealed Syrian refugees' heavy dependence and preferences for information sources such as friends and family. In the U.S., Hassan and Wolfram (2020) investigated the information needs and seeking behaviors of African refugees in the Midwest United States. The participants reported requiring information related to housing, health care, employment and education and relied heavily on their caseworkers employed as sources of information after their arrival in the United States.…”
Section: Information Crafting and Immigrants In Canadamentioning
confidence: 99%
“…When both groups arrive to the host country, they recognize an urgent need for information about housing, transportation, education, employment, social services, and healthcare. They are bound to receiving information from their small world (e.g., family, friends, ethnic society members) through informal channels, or through limited access to the outside world via formal sources of information (e.g., medical professionals, lawyers, social workers, mass media, public libraries, non‐governmental organizations, detention centers, refugee camps) (Fisher, Durrance & Hinton, 2004; Hassan & Wolfram, 2020; Oduntan & Ruthven, 2020; Solberg & Peters, 2020; Wang, Huang, Li, & Chen, 2020; Zimmerman & Beam, 2020; Zimmerman, 2018).…”
Section: Panel Formatmentioning
confidence: 99%